PERBUATAN SEKSUAL ATAS DASAR SUKA SAMA SUKA DI LUAR PERKAWINAN (Kajian Perspektif Hukum Pidana dan Hukum Islam) - Arya Candra Abhitama; Kuswardani Kuswardani (Legal Standing : Jurnal Ilmu Hukum, 2023)
Violence in English is called violence, which is a diction which includes the phrase vis so that it has a definition of power and power, then latus which has the definition of bringing. The problem to be studied in this paper is how to regulate consensual sexual acts outside of marriage according to criminal law and Islamic law. With this writing, it aims to find out how the law regulates consensual sexual acts. Sexual acts which are carried out voluntarily can be punishable by crime when carried out with a husband or wife who has intercourse with the opposite sex who is not a married partner or with someone where it is known or suspected that the person is not yet an adult. Protection of victims of acts of consensual acts against minors who are not in marriage can be prosecuted under Article 293 paragraph (1) of the Criminal Code (KUHP) where a minor is based on Article 330 of the Civil Code, namely a person who has not reaching the age of 21 have never been married. In Islam there is a desire for normal and free sexual relations with marriage ties with the intention of worshiping Allah. Islam views sexual relations with no sacred ties or marriage as something that is said to be vile.